IDENTIFIKASI FAKTOR YANG MEMENGARUHI ANAK PUTUS SEKOLAH DI KABUPATEN BADUNG - CAHYANI, NI KOMANG AYU SRI; SUCIPTAWATI, NI LUH PUTU; SUKARSA, KOMANG GDE (E-Jurnal Matematika, 2019)
School dropout is someone who has left school before she/he has  finished her/his study. This research aims to identify the factors that affects school dropout in Badung Regency. The research method used is confirmatory factor analysis and obtained six factors that affects school dropout, namely the lack of interest and willingness of children to go to school, the view that school is considered unattractive by student, inability to take lessons, economic family, lack of parental attention, and children’s play environment. The results of factor analysis which shows that the most dominant factor that affects school dropout in junior high school level is lack of parental attention, in senior high school the factors are lack of interest and willingness of children to go to school.